Kajian Karakteristik dan Evaluasi Pasca Huni Bangunan Pasar - Lisna Syadiah; Danang Harito Wibowo (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2020)
This research examines in detail and academically the characteristics of the Paramount Modern Market, then conducts a post-occupational evaluation on the Paramount Modern Market building comprehensively. The object of study was chosen based on its location in the commercial superblock area, market design evolution, and in Gading Serpong commercial area there was an acceleration of economic growth. This study discusses the analysis of the application of the concept of green city in cluster dwellings in Gading Serpong. The method used in this study is a descriptive qualitative method that is carried out with a case study approach, as well as using inductive post-occupational evaluation techniques. The research found are the characteristics of the spatial, technical, and stylistic systems of the Paramount Market building are already efficient, quite in accordance with established rules, and can support trading activities on the market well and efficiently, and then the post-occupatonal evaluation results state that most of the elements in technical, functional and behavioral approaches are efficient and functioning optimally.